Embracing AI in education: shaping the future of learning - Amzah, Rodhiah; Halim, Nurul Syafawani; Nik Mat, Nik Mahfuzah; Mohd Salim, Mohd Nur Fitri; Yusuf, Asmahanim (Universiti Teknologi MARA, Negeri Sembilan, 2025)
What are we without the internet? Can we live without it? Will it make a difference in education if we do not use it at all? There is no doubt that a mobile phone is a must-have item for everyone, and the digital world has made it impossible to live without one. The use of Artificial Intelligence (AI) in education has expanded and become increasingly prevalent over the years. It has emerged as a transformative tool, working effectively across various fields and industries. Undoubtedly, AI has been widely accepted and normalised in education, with its use growing over time. AI is gradually becoming the new Google, as 69% of students reported using it as a search engine, with ChatGPT being the most popular AI tool, followed by Grammarly, Google Gemini, and Perplexity (Ward, 2024). Thus, AI has made a significant contribution to education by offering benefits and experiences that can enhance the learning process. Most educational institutions have nowadays adopted and adapted AI as part of the new era of digital learning.